Prevalencia de Mycobacterium spp. en canales de bovinos faenados en el matadero municipal del cantón Chone - García Espinales, Katherine Elizabeth (2021)
The present investigation was carried out in order to determine the prevalence of Bovine Tuberculosis in carcasses of cattle slaughtered in the municipal slaughterhouse in Chone canton, taking into account that this is an infectious disease whose main host is bovine cattle and this in turn, it is zoonotic, the causative agent is Mycobacterium spp. This research was carried out in the municipal slaughterhouse in Chone canton, where it was possible to identify lesions in lymph nodes typical of Bovine Tuberculosis, carrying out the sampling in the months from January to April 2020 with a population of 229 bovines from Chone canton and neighbor cantons, this research consisted of observing the slaughter process of the bovines and subsequently taking samples of the affected lymph nodes through post-mortem inspection, the second phase of the research was developed in the laboratory of the National Institute of Public Health Research - INSPI- Dr. Leopoldo Izquieta Pérez located in Guayaquil city where the microbiological diagnosis was carried out using culture media (Stonebrink and Ogawa Kudoh) which are specific for Mycobacterium bovis due to the efficacy they have for the diagnosis of this disease, then the Ziehl Neelsen stain was performed, which is a fast differential technique, very effective for the detection of Bovine Tuberculosis, where it was possible to establish a prevalence of 0.87% (2/229) of bovine Tuberculosis in the municipal slaughterhouse in Chone canton, being considered low.